THE CONSTRUCTION OF A CORP IN THE SET OF POINTS IN A LINE OF DESARGUES AFFINE PLANE - Filipi, Kristaq; Zaka, Orgest; Jusufi, Azir (Matematichki Bilten, 2019)
In the article [1], we show that the set of points on a line, in the affine Desargues plans, connected with addition forms an Abelian group. In this article, we will define multiplication of points on a line in the affine Desargues plans. We will show that this set forms a multiplicative group. And we will show that every straight line of Desargues affine plans, along with both addition and multiplication operations, forms the corp (skew-field).